2016
DOI: 10.3109/0886022x.2016.1145521
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ability of bone marrow derived cells to engraft the kidney and promote renal tubular regeneration in mice following exposure to cisplatin

Abstract: It has been suggested that bone marrow derived stem cells have the ability to engraft the kidney and improve the outcome of severe acute kidney injury (AKI) in mice exposed to high doses of cisplatin, providing hope for cancer patients in whom irreversible renal damage occasionally occurs following the use of this highly effective anti-tumor drug. We tested the therapeutic potential of bone marrow derived cells injected during the acute phase (day 3 after cisplatin administration) of experimentally-induced AKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…In mammals, nephrons are limited in number because nephron formation ceases before birth or in the neonatal period. In humans, the ability of regeneration and repair of the kidney is attenuated around 35 weeks of gestation due to the depletion of precursor mesenchymal cells, resulting in no new nephron formation [ 20 , 21 ]. In this study, we collected the samples from children with congenital hydronephrosis at different ages, and our results suggest that CD133 expression is closely associated with the age of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, nephrons are limited in number because nephron formation ceases before birth or in the neonatal period. In humans, the ability of regeneration and repair of the kidney is attenuated around 35 weeks of gestation due to the depletion of precursor mesenchymal cells, resulting in no new nephron formation [ 20 , 21 ]. In this study, we collected the samples from children with congenital hydronephrosis at different ages, and our results suggest that CD133 expression is closely associated with the age of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we noticed that clinical signs or mortality of animals in cisplatin nephrotoxicity studies are rarely reported. Moreover, we even found statement that “renal failure per se is not painful” [ 191 ].…”
Section: Challenges Of Cisplatin Rodent Modelmentioning
confidence: 99%
“…Cheng et al studied biodistribution and found that one hour after iv injection of syngeneic MSCs most of the radiolabeled (or GFP labeled) cells were trapped in the lungs (62%), followed by liver (12.5%), spleen (11.4%), and kidneys (5.4%), but 7 days after injection no signs of MSCs in any organ was found [ 36 ]. Studies using GFP labeling reported disappearance of GFP + cells in the kidney 4 days after injection [ 22 , 31 ], while studies that used PKH26 [ 12 , 33 ] or CM-Dil [ 13 ] labeling reported presence of positive cells in the kidney until the end of their study, that is, 2–4 wks. Nevertheless, the fact that injected MSCs are mostly trapped in the lungs and cleared without any engraftment in kidney raise questions regarding their pathophysiologic mechanisms, as well as possibility of their potential rejection by the host's immune system.…”
Section: Reliability Of Tracking the Injected Cellsmentioning
confidence: 99%
“…First, acute rejection of injected cells in cisplatin model was not evaluated nor reported. It was only reported that cells disappeared within 24 h after injection [ 18 , 22 , 31 ], which could suggest acute rejection. However, sensitization reaction (mixed-lymphocyte reaction—MLR test) that could confirm or omit immune reaction was not done in any of AKI studies.…”
Section: Mscs and Risk Of Immune Rejectionmentioning
confidence: 99%
See 1 more Smart Citation